Parallax adjustment for visual comfort enhancement using the effect of parallax distribution and cross talk in parallax-barrier autostereoscopic three-dimensional display - Kim, Donghyun; Lee, Hyoung; Kim, Sung-Kyu; Sohn, Kwanghoon (SPIE-SOC PHOTO-OPTICAL INSTRUMENTATION ENGINEERS, 2015)
Visual discomfort is a common problem in three-dimensional (3D) videos, and this issue is the subject of many current studies. Among the methods to overcome visual discomfort presented in current research, parallax adjustment methods provide little guidance in determining the condition for parallax control. We propose a parallax adjustment based on the effects of parallax distribution and cross talk on visual comfort, where the visual comfort level is used as the adjustment parameter, in parallax-barrier-type autostereoscopic 3D displays. We use the horizontal image shift method for parallax adjustment to enhance visual comfort. The speeded-up robust feature is used to estimate the parallax distribution of 3D sequences, and the required amount for parallax control is chosen based on the predefined effect of parallax distribution and cross talk on visual comfort. To evaluate the performance of the proposed method, we used commercial 3D equipment with various intrinsic cross-talk levels. Subjective tests were conducted at the fixed optimal viewing distance for each piece of equipment. The results show that comfortable videos were generated based on the proposed parallax adjustment method. (C) 2015 Society of Photo-Optical Instrumentation Engineers (SPIE)